Father Absence and the Educational Gender Gap - Shelly Lundberg (Institute of Labor Economics (IZA), 2017)
The educational attainment of young women now exceeds that of young men in most of the developed world, and women account for about 60% of new four-year college graduates in the United States. Several studies have suggested that the increase in single-parent households may be contributing to the growing gender gap in education, as boys are more vulnerable to the negative effects of father absence and economic disadvantage than girls. Using data on recent cohorts of young men and women from the National Longitudinal Study of Adolescent to Adult Health (Add Health), I find evidence consistent with other studies that boys are relatively more likely to experience problems in school, including school suspensions, when their father is absent, but also that girls are relatively more likely to experience depression in adolescence, particularly in step-father families. By the time Add Health subjects are young adults, there is no evidence that father absence early in life is more strongly associated with lower rates of college graduation for men, compared to women, in either cross-sectional or family fixed-effect models.
Keywords: I20; J12; J16; 330; father absence; family structure; gender; college graduation; education; school quality